“Evaluación post - implementación de un sistema de riego por aspersión en el cultivo de cacao (theobroma cacao l.) en la ESPAM-MFL” - Mendoza Vera, María Isabel (2012)
This work consisted in evaluated an sprinkler irrigation system after – installation in the cocoa crop, the main objective was to determine the efficiency of system operation, evaluating the uniformity of distribution, uniformity coefficient, coefficient of variation, efficiency discharge pressures, flows, etc. The result of this evaluation was a Christiansen uniformity coefficient of 97%, considered relatively high. Uniformity of distribution (UD) with 27% characterized as unacceptable. The discharge efficiency (Ed) of 63% considered relatively low in this system. And a variation coefficient (CV) of 74% unrealistically high value. The distribution uniformity (DU) is affected by other factors such as wind speed, the flow delivered, and the inlet pressure, the leaves of the crop, banana trees, and others. The irrigation manual watering should be done keeping the system and the results of agronomic design must be concluded that daily irrigation ranging between 4.80 and 3.00 min daily at a rate that varies between 817 and 634 L / h for all system. Furthermore, this system is designed to work three sides or 25 sprinklers.